Perspectives on climate policies - Fredrik N. G. Andersson (Lund University, School of Economics and Management, LUSEM Sustainability Research Network, 2019)
The purpose of this article is twofold: First to discuss three misconceptions in the debate on climate policies: i) that de-growth is necessary, ii) that the market economy is part of the problem rather than part of the solution to climate change, and iii) that the only policy tool needed is to price carbon emissions. Second, to argue that climate change cuts across traditional policy areas and that a wide set of different policy tools is required to reduce emissions. I also call for sequential policies that begin by enabling decarbonization before focusing on phasing out emissions.
Keywords: Q50; Q54; Q56; Q58; E6; 330; climate change; policy; carbon tax; economic development; growth